Intranasal inactivated influenza vaccines for the prevention of seasonal influenza epidemics - Kaori Sano; Akira Ainai; Tadaki Suzuki; Hideki Hasegawa (Taylor & Francis Group, 2018)
Introduction: Intranasal influenza vaccines are expected to confer protection among vaccine recipients by successful induction of mucosal immune response in the upper respiratory tract. Though only live attenuated influenza virus vaccines (LAIVs) are licensed and available for intranasal use in humans today, intranasal inactivated influenza vaccines (IIVs) are currently under reconsideration as a promising intranasal influenza vaccine. Areas covered: This review addresses the history of intranasal IIV research and development, along with a summary of the studies done so far to address the mechanism of action of intranasal IIVs. Expert commentary: From numerous in vitro and in vivo studies, it has been shown that intranasal IIVs can protect hosts from a broad spectrum of influenza virus strains. In-depth studies of the mucosal antibody response following intranasal IIV administration have also elucidated the detailed functions of secretory IgA (immunoglobulin A) antibodies which are responsible for the mechanism of action of intranasal vaccines. Safe and effective intranasal IIVs are expected to be an important tool to combat seasonal influenza.